PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTU STRATEGI GAME MAZELABIRIN DAN PUZZLE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS X MIPA 3 SMA N 1 BADEGAN - Alfi Safangati; Uki Suhendar (Universitas Muhammadiyah Ponorogo, 2020)
Problems in the class X MIPA 3 of SMA Negeri 1 Badegan is student have not been able to apply concepts, classify objects, and make good use of operating procedures. This shows that students' understanding in mathematical concepts is still low. This study aims to describe the application of problem based learning model assisted by game mazelabirin and puzzle to improve students understanding of the mathematical concept of class X MIPA 3 students in SMA Negeri 1 Badegan. This type of research was Classroom Action Research (CAR). The subjects of this study were 34 students of Class MIPA 3 of SMA Negeri 1 Badegan. The students consisted of 9 male students and 25 female students. The analytic data understanding of students' mathematical concepts were taken from the results of tests understanding mathematical concepts and learning management data were taken from the learning management observation sheet. The instrument used was a matter of concept comprehension test and observation management learning sheet. The results of this study were the application of Problem Based Learning models assisted by Game Mazelabirin and Puzzle cauld improve students' understanding of the concepts. This application started from the teacher who gove problems, students in groups, then discussing to solve problems with puzzle games or mazelabirin, then the results of the discussion were delivered in front of the class, the teacher provided reinforcement and drews in conclusions with students. The researchers made improvements with the first thing students were taught the importance of understanding the material and the spirit of learning. Provide column completion steps on the LKS answer sheet. Give questions that require understanding to be constructed in the form of mathematics. Keywords: Problem Based Learning (PBL) Model; Game Mazelabirin and puzzle; Understanding Mathematical Concepts